Acquired neuromyotonia in children with CASPR2 and LGI1 antibodies. (6th February 2019) - Surana, Snehal; Kumar, Ratna; Pitt, Matthew; Hafner, Patricia; Mclellan, Ailsa; Davidson, Joyce; Prabakhar, Prab; Vincent, Angela; Hacohen, Yael; Wright, Sukhvir
Abstract : Acquired neuromyotonia is a form of peripheral nerve hyperexcitability. In adults, pathogenic antibodies that target the extracellular domains of leucine‐rich glioma‐inactivated protein 1 (LGI1) and contactin‐associated protein‐like 2 (CASPR2) have been reported. We describe three paediatric patients with acquired neuromyotonia and CASPR2 and LGI1 serum antibodies. They all presented with acute‐onset myokymia and pain in the lower limbs; one patient also had muscle weakness. Electromyography was suggestive of peripheral nerve hyperexcitability. Two patients improved without immunotherapy; one treated patient remained immunotherapy‐dependent. Although not fatal, acquired paediatric neuromyotonia can be disabling. It is amenable to symptomatic treatment or may undergo spontaneous recovery. More severe cases may require rational immunotherapy. What this paper adds: The symptoms of neuromyotonia may resolve spontaneously or may require sodium channel blockers. Patients with debilitating symptoms who are refractory to symptomatic therapy may require immunotherapy. What this paper adds: The symptoms of neuromyotonia may resolve spontaneously or may require sodium channel blockers. Patients with debilitating symptoms who are refractory to symptomatic therapy may require immunotherapy. This article's abstract has been translated into Spanish and Portuguese. Follow the links from the abstract to view the translations. Resumen: Neuromiotonía adquirida en niños con anticuerpos CASPR2 y LGI1: La neuromiotonía adquirida es una forma de hiperexcitabilidad de los nervios periféricos. En algunos adultos, se han notificado anticuerpos patógenos que se dirigen a los dominios extracelulares de la proteína 1 inactivada por glioma rico en leucina (LGI1) y la proteína 2 asociada a contactina (CASPR2). Describimos tres pacientes pediátricos con neuromiotonía adquirida y anticuerpos séricos CASPR2 y LGI1. Todos presentaban mioquimia de inicio agudo y dolor en las extremidades inferiores; un paciente también tenía debilidad muscular. La electromiografía sugirió hiperexcitabilidad del nervio periférico. Dos pacientes mejoraron sin inmunoterapia; un paciente tratado permaneció dependiente de la inmunoterapia. Aunque no es fatal, la neuromiotonía pediátrica adquirida puede ser incapacitante. Es susceptible de tratamiento sintomático o puede sufrir una recuperación espontánea. Los casos más graves pueden requerir inmunoterapia racional. Resumo: Neuromiotonia adquirida em crianças com anticorpos PRCAS2 e GIL1: A neuromiotonia adquirida é uma forma de hiperexcitabilidade nervosa periférica. Em alguns adultos, anticorpos patogênicos que visam os domínios extracelulares da proteína glioma‐inativada rica em leucina1 (GIL1) e da proteína contactina‐associada 2 (PRCAS2) foram reportados. Descrevemos três pacientes pediátricos com neuromiotonia adquirida e anticorpos séricos PRCAS2 e GIL1 CASPR2. Todos apresentaram miocimia de início agudo e dor nos membros inferiores; um paciente também teve fraqueza muscular. A eletromiografia foi sugestiva de hiperexcitabilidade nervosa periférica. Dois pacientes melhoraram sem imunoterapia; um paciente tratado permaneceu imunoterapia‐dependente. Embora não seja fatal, a neuromiotomia pediátrica aguda pode ser incapacitante. É responsiva a tratamento sintomático e pode apresentar recuperação espontânea. Casos mais severaos podem requerer imunoterapia racional.